Qué revistas médicas españolas leen y cómo se informan los médicos de atención primaria() - González de Dios, Javier (Aten Primaria, 2011)
OBJECTIVE: To determine which medical journals are read by Primary Care doctors, their language preferences, publication format and the ways of accessing them. DESIGN: Telephone interview. LOCATION: All the autonomous communities of Spain. PARTICIPANTS: A total of 300 Primary Care physicians selected by proportional stratified sampling by autonomous community and type of professional (general practitioners and paediatricians). MEASURES: A structured 18-question survey on reading habits administered by telephone using computer-assisted techniques. RESULTS: Respondents declared they preferably read specialty journals and are inclined to the printed format, although the online version is the option of younger doctors and paediatricians. The general practitioners prefer to read case studies (73%) and paediatricians opt for the reviews (74%). Overall, 48% read 1 to 4 articles per week. The search tools preferred by 70% of respondents were Google and Yahoo, followed by databases (29%). Eighty eight per cent stated an interest in having a free online service to find quality Spanish journals. As regards language, 80% find it more useful to read articles in Spanish than in English, and 70% believe that there are no quality differences between the publications in both languages. CONCLUSIONS: The publications in Spanish are used as the preferred sources of information by a high percentage of Primary Care physicians. These professionals believe that Spanish-language databases make it easier to access these publications, and are useful and necessary for professional practice.